2020
DOI: 10.1111/echo.14818
|View full text |Cite
|
Sign up to set email alerts
|

Relation between left atrial strain and exercise tolerance in patients with mild mitral stenosis: An insight from 2D speckle‐tracking echocardiography

Abstract: Background Mild mitral stenosis (MS) is a progressive disease but unfortunately, its clinical course is still unclearly studied. We aimed to study the left atrial (LA) deformation in such patients and how it is related to exercise intolerance. Methods Seventy‐five patients with mitral valve area of 1.81 ± 0.13 cm2 and 40 healthy control subjects were enrolled. All participants had sinus rhythm, and they underwent conventional echocardiography and LA strain analysis with speckle‐tracking study. The following pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Mahfouz et al performed stress echocardiography to assess exercise intolerance in 75 patients with MV area of 1.81 ± 0.13 cm 2 and compared them with 40 healthy control subjects. Interestingly, 44% of asymptomatic patients with mild MS had exercise intolerance, and reservoir strain was significantly associated with exercise capacity in patients with mild MS (cut-off value: reservoir strain ≤ 26.5%) ( 46 ). Similarly, Chien et al investigated the relationship between LA deformation as measured by 2DSTE derived LA strain and HF symptoms in 69 subjects with rheumatic MS, and found that NYHA class independently correlated with LA reservoir strain and reservoir strain rate ( 149 ).…”
Section: La Mechanics In Hf Stagesmentioning
confidence: 99%
“…Mahfouz et al performed stress echocardiography to assess exercise intolerance in 75 patients with MV area of 1.81 ± 0.13 cm 2 and compared them with 40 healthy control subjects. Interestingly, 44% of asymptomatic patients with mild MS had exercise intolerance, and reservoir strain was significantly associated with exercise capacity in patients with mild MS (cut-off value: reservoir strain ≤ 26.5%) ( 46 ). Similarly, Chien et al investigated the relationship between LA deformation as measured by 2DSTE derived LA strain and HF symptoms in 69 subjects with rheumatic MS, and found that NYHA class independently correlated with LA reservoir strain and reservoir strain rate ( 149 ).…”
Section: La Mechanics In Hf Stagesmentioning
confidence: 99%
“…reservoir, conduit and contractile strain suggestive of severe LA dysfunction in patients with severe rheumatic MS when compared to healthy controls. It has been shown in a previous study by Mahfouz et al 17 on 75 patients that the conduit and reservoir function are affected in mild MS while LA contractile strain is well preserved. The increased LA contractile function appears as a compensatory mechanism to counterbalance reduced LA reservoir and conduit function in mild MS as LV filling predominantly occurs in LA contractile phase in MS in contrast to normal filling pattern where LA filling predominantly occurs in the early conduit phase.…”
Section: Discussionmentioning
confidence: 84%
“…Our study demonstrates a significant decrease in all three left atrial strain parameters i.e. reservoir, conduit and contractile strain signifying severe LA dysfunction in patients with severe rheumatic MS. Mahfouz et al 5 reported that in mild MS, LA conduit and reservoir strain were decreased but the contractile strain was well preserved. Another study by Demirkol et al 6 on 52 asymptomatic MS patients with MVA 1.38 ± 0.36 cm 2 and mean diastolic transmitral gradient 7.9 ± 2.8 mm Hg also reported reduced LA reservoir and conduit strain but increased contractile strain.…”
Section: Discussionmentioning
confidence: 99%
“…two-dimensional (2D) speckle tracking echocardiography (STE). 4 , 5 , 6 Most previous studies have either assessed global LA strain, reservoir or conduit strain with contractile strain being reported only in mild to moderate MS. 5 , 6 We aimed to assess LA function (reservoir, conduit strain and contractile strain) by STE and its correlation with NYHA functional class and echocardiography parameters in patients with isolated severe MS with pulmonary hypertension and healthy controls.…”
Section: Introductionmentioning
confidence: 99%